Anti-inflammatory and anti-diabetic properties of plant extracts and compounds from Scabiosa columbaria and Sclerocarya birrea - Maharaj, Dashnie Naidoo (University of Pretoria, 2024)
Thesis (PhD (Chemistry))--University of Pretoria, 2023.